A clinical study on the analysis of caesarean section rates using Robson’s ten group classification in a tertiary care hospital - Shankar, Priya; J., Madhu; Raju, Vinay (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Auditing c section rates can be done using Robson’s classification which in turn helps achieve a uniform basis for comparison across centers and across various countries. Methods: A retrospective analysis was done in a tertiary care hospital in north Karnataka KIMS, over a period of 6 months May 2017 to October 2017. All cases of LSCS done during this period were classified according to Robson’s classification and analyzed. Results: Out of 5080 overall deliveries 1876 delivered by cesarean section attributing to 36.76% cesarean section rate. Highest contribution was from group 5 (36%) and group 2 (19.24%). Conclusions: Robson’s classification helps to identify and analyze the group that contribute to the most to overall cesarean section rate and this helps us to modify strategies and interventions to optimize cesarean section rate.